Gastric juice piR‐1245: A promising prognostic biomarker for gastric cancer. Issue 4 (28th November 2019) - Zhou, Xiaorong; Liu, Jianhong; Meng, Aifeng; Zhang, Lihong; Wang, Min; Fan, Hong; Peng, Wei; Lu, Jianwei
Abstract: Background: Emerging reports demonstrated that PIWI‐interacting RNAs (piRNAs) played an indispensable role in tumorigenesis. However, it still remains elusive whether piR‐1245 in gastric juice specific in stomach could be employed as a biomarker for gastric cancer (GC). The present work is aiming at exploring the possibility of piR‐1245 in gastric juice as a potential marker to judge for diagnosis and prognosis of gastric cancer. Methods: Gastric juice was collected from 66 GC patients and 66 healthy individuals. Quantitative real‐time reverse transcriptase polymerase chain reaction (qRT‐PCR) was employed to measure the levels of piR‐1245 expression. Then, the pattern of piR‐1245 expression in gastric juice was determined between GC patients and healthy individuals. A receiver operating characteristic (ROC) curve was constructed for distinguishing GC from healthy individuals. Results: Gastric juice piR‐1245 levels in GC were higher than those of controls ( P < .0001). The value of area under ROC (AUC) was 0.885 (sensitivity, 90.9%; specificity, 74.2%; 95% confidence interval, 0.8286 to 0.9414). High gastric juice piR‐1245 expression was signally correlated with tumor size ( P = .013) and TNM stage ( P = .001). GC patients with high piR‐1245 expression in gastric juice exerted a poorer overall survival (OS) ( P = .0152) and progression‐free survival (PFS) ( P = .013). COX regression analysis verified that gastric juice piR‐1245 expression was an independent prognostic risk variable for OS ( P < .05). Conclusions: The current study suggested that piR‐1245 in gastric juice had the potential to be a useful biomarker for GC detection and prognosis prediction.